B-RAF and its novel negative regulator reticulocalbin 1 (RCN1) modulates cardiomyocyte hypertrophy. (2nd February 2014) - Kramann, Nadine; Hasenfuß, Gerd; Seidler, Tim
Abstract: Aim: Activation of the kinase RAF and its downstream targets leads to cardiomyocyte hypertrophy. It has been hypothesized that B-RAF might be the main activator of MEK in various cell types. Therefore, the aim of this study was to investigate the role of B-RAF and its modulating factors in cardiomyocyte hypertrophy. Methods and results: Neonatal rat cardiomyocytes were pre-treated with and without the specific B-RAF inhibitor SB590885 and then stimulated with phenylephrine to induce hypertrophy. Inhibition of B-RAF completely impeded the hypertrophic response and led to a significant reduction of MEK1/2 phosphorylation. By applying a eukaryotic cDNA expression screen, based on a dual-luciferase reporter assay for B-RAF activity measurement, we identified RCN1 as a new negative modulator of B-RAF activity. Adenovirus-mediated overexpression of reticulocalbin 1 (RCN1) completely impeded phenylephrine-induced hypertrophy and led to significantly reduced MEK1/2 phosphorylation. Conversely, adenoviral knockdown of RCN1 with a specific synthetic miRNA induced cardiomyocyte hypertrophy and significantly increased MEK1/2 phosphorylation. Conclusions: In summary, our results show that the inhibition of B-RAF abolishes cardiomyocyte hypertrophy and we identified RCN1 as novel negative modulator of cardiomyocyte hypertrophy by inhibition of the mitogen-activated protein kinase signalling cascade. Our results show that B-RAF kinase activity is essential for cardiac hypertrophy and RCN1, its newly identified negative regulator, abolishes hypertrophic response of cardiomyocytes in vitro .